Hypnohterapy to Reduce Stress and Total Cholesterol Blood Levels in the Elderly - Artia Diarina; Romalina Romalina; Adil Candra (Aloha International Journal of Health Advancement (AIJHA), 2020)
Management of degenerative diseases in the elderly needs specific and comprehensive treatment. The development of complementary therapies has recently been in the spotlight of many countries. Some scientists speculate that hypnotherapy can change an individual's acceptance of pain or other physical symptoms. This study aimed to determine the effect of hypnotherapy on changes in stress levels and total blood cholesterol levels in the elderly at Posyandu Kaswari and Garuda in the Tanjungunggat Health Center. This study used a non-randomized control group pretest and posttest design. The sample consisted of 30 older adults, 15 in the experimental group and 15 in the control group. Data were collected using a blood cholesterol test kit and the Kessler Psychological Distress Scale instrument. The bivariate analysis showed that hypnotherapy's effect on reducing stress levels and total cholesterol blood levels of the elderly at Posyandu Kaswari, Tanjungunggat Health Center. It is recommended to socialize hypnotherapy to the public and establish it as an independent nursing intervention to improve the quality of human life in hospitals and the community. Keywords: hypnotherapy; stress; cholesterol